Essential of pharmacotherapeutics - Barar, F. S. K. (New Delhi, 2009)
Essentials of Pharmacotherapeutics is a collection of fundamental concepts of the subject, aiming at the safe and effective use of drugs in the treatment of disese.
Keywords: PHARMACOTHERAPEUTICS; Pharmacology